Opto-Microfluidic Immunosensors: From Colorimetric to Plasmonic - He, Jie-Long (Micromachines (Basel), 2016)
Optical detection has long been the most popular technique in immunosensing. Recent developments in the synthesis of luminescent probes and the fabrication of novel nanostructures enable more sensitive and efficient optical detection, which can be miniaturized and integrated with microfluidics to realize compact lab-on-a-chip immunosensors. These immunosensors are portable, economical and automated, but their sensitivity is not compromised. This review focuses on the incorporation and implementation of optical detection and microfluidics in immunosensors; it introduces the working principles of each optical detection technique and how it can be exploited in immunosensing. The recent progress in various opto-microfluidic immunosensor designs is described. Instead of being comprehensive to include all opto-microfluidic platforms, the report centers on the designs that are promising for point-of-care immunosensing diagnostics, in which ease of use, stability and cost-effective fabrication are emphasized.